Ghana’s agricultural transformation: Past patterns and sources of change - Hazell, Peter B. R.; Diao, Xinshen; Magalhaes, Eduardo (International Food Policy Research Institute, 2019)
The future sustainability of the current patterns of agricultural growth is constrained by the availability of remaining virgin and fallow land for future expansion of the cropped area. As the land frontier runs out, farmers will need to shift towards more intensive modes of production, and options will need to include higher-yielding technologies and a greater focus on high-value products. The economic viability of these options will depend on government policies towards agricultural R&D, infrastructure, and value chain interventions that condition access to modern inputs and urban markets and their costs, and trade policies that condition the level of competition farmers must face in their domestic markets. These policies will need to be cognizant of the needs of the changing nature of Ghanaian agriculture. As more small farm households are attracted into nonfarm activities, farms become more consolidated, rural wages rise, and rural youth become better educated, more emphasis will be needed on the development of technologies and commercial farming practices that raise land as well as labor productivity, are attractive to young farmers, and meet the needs of Ghana’s increasingly urbanized food system.